On the nonlinear dynamics of a circular dielectric elastomer oscillator. (6th June 2019) - Cao, Chongjing; Hill, Thomas L; Conn, Andrew T
Abstract: Dielectric elastomer actuators (DEAs) are an emerging soft actuation technology that have advantages in large actuation strain, inherent compliance and low cost. Resonant actuation of DEAs has been shown to increase the actuation stroke and power output and has been utilized in applications such as robotic locomotion and loudspeakers. In this work, we present a planar circular dielectric elastomer oscillator (DEO) that can exert out-of-plane deformation as large as 80% of its own diameter at resonance. By experiments and model simulation we show that this simple DEO design exhibits complex nonlinear responses, including multiple solutions, sub- and super-harmonics, and exhibits multiple resonant peaks. The DEO performance is characterized against membrane pre-stretch and the weight of the attached mass and its actuation signals (DC and AC amplitudes). The resonant frequency and the amplitude are found to be easily tuned by varying these parameters. Such large stroke output and highly tunable resonance make this DEO a promising candidate for applications such as active vibration absorption, embedded loudspeakers, soft pumps and robotic locomotion.